Willingness to pay for the rural telephone service in Bangladesh and Peru - Maximo Torero; Shyamal K. Chowdhury; Virgilio Galdo (University of Bonn, Center for Development Research (ZEF), 2002)
This paper measures the rural households' willingness to pay (WTP) for access to public telephone services in Bangladesh and Peru through contingent valuation methods. The development of contingent valuation methods together with the econometric expansion of qualitative response models has permitted an approximation to the consumer surplus in the presence of externalities, public good and information asymmetries. The paper utilizes both parametric and nonparametric estimations that are commonly observed in the literature concerned with the estimation of WTP. The main result of the paper suggest that rural telecommunications projects are welfare enhancing, since households' WTP are higher than the prevailing tariff rates. For Peru, households' currently pay US0.14 for local calls and US 0.29 for national long distance calls (LDN), while their WTP for a local call varies from US0.25 to US0.35, and for a LDN call varies from US0.33 to US0.45. For Bangladesh, households' WTP for a local call varies from US0.10 to US0.26, for a LDN call from US0.23 to US0.50, and for an international call from US0.93 to US1.35. Meanwhile, they are currently paying US 0.03, US 0.06 and US 0.46 respectively. Despite the fact that the monetary measures of WTP vary depending on measurement methods, the results are consistent for all the parametric and non-parametric measures utilized suggesting that the rural telecommunications projects in Bangladesh and Peru are directly contributing to the improvement of welfare of rural households.
Keywords: 330; Consumer/Household Economics; Willingness to pay; Netzregulierung; Telefon; Ländlicher Raum; Bangladesch; Peru